OVERVIEW OF THE MARKET ABUSE REGULATION UNDER THE FINANCIAL MARKETS ACT 19 OF 2012 - Howard Chitimira (Obiter, 2014)
This paper analyses the regulation of market abuse under the Financial Markets Act 19 of 2012 in order to investigate the adequacy of such regulation as regards to the combating of market-abuse practices in South Africa. To this end, the paper provides an overview analysis of the market abuse (insider trading and market manipulation) offences as well as the penalties and other anti-market abuse-enforcement approaches that are employed under the Financial Markets Act 19 of 2012 in a bid to provide a revamped and adequate anti-market abuse regulatory and -enforcement framework in South Africa. Moreover, where possible, the paper also provides a comparative analysis of these offences, penalties and other anti-market abuse-enforcement approaches and those that were provided under the Securities Services Act 36 of 2004. This is done to examine whether the anti-market abuse regulatory and -enforcement framework that was re-introduced under the Financial Markets Act 19 of 2012 has now adequately resolved the flaws and gaps that were associated with a similar framework under the former Act.